The Development of Educational Game’s Activity Management through Local Natural Media Encouraging Early Childhood’s Analytical Thinking - Keawpoka, Rapipan; Chaiyapat, Sopa; Dajong, Yanin (NEU ACADEMIC AND RESEARCH JOURNAL, 2024)
The purposes of this research were to 1) determine the efficiency of activities based on high-scope concept using local natural media that enable to promote analytical thinking of early childhood students, 2) compare analytical thinking of early childhood students before and after organizing activities according to high-scope concept using local natural media. The sample group consisted of 10 male and female early childhood students (aged between 4 - 5 years) who were studying in the second year of early childhood education in the second semester of the academic year 2022 at Ban Kew Dong Mafai School, Phen district, UdonThani province, with the total number of 10samples which were obtained by cluster random sampling. The research tools consisted of 1) 3 plans for game activity according to high-scope concept, namely: Map 1 The little baby who observed; Map 2 the little baby who organized, Map,3 the little baby who understood, 2) the analytical thinking test of early childhood student to test analytical thinking skills of early childhood students, 15 items. The statistics were used for analyzing the data comprised frequency, percentage, mean, standard deviation, and testing of hypothesis by t-test. The research results were found that: 1) The efficiency of educational game and activities of high-scope concept using local natural media promoting the early childhood student’s analytical thinking skills was at 80.00/92.67 that was higher than the specific criteria, and 2) The efficiency index of high-scope concept using local natural media was higher than the pre-test result both in overall and each aspect with the statistical significance at 0.05.